Analysis of Service Excellence, Customer Satisfaction, and Promotion toward Customer Loyalty of Retail MSMEs - Rizky Muyasar; Syamsudin Baharsyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid growth of retail micro, small, and medium enterprises or MSMEs in Indonesia has intensified business competition, requiring business actors to implement service excellence, effective promotional strategies, and customer satisfaction to build long-term customer loyalty. This study aims to analyze the effect of service excellence, customer satisfaction, and promotion on customer loyalty of retail MSMEs in Cikeas Udik Village. This research employed a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 78 respondents selected using proportional random sampling from a population of 312 retail MSMEs. The research instruments were tested for validity and reliability, followed by classical assumption tests, t-tests, F-tests, and coefficient of determination analysis. The results indicate that service excellence, customer satisfaction, and promotion have a positive and significant effect on customer loyalty, both partially and simultaneously. These findings suggest that improving service quality and implementing appropriate promotional strategies can enhance customer satisfaction and strengthen customer loyalty. Therefore, retail MSMEs are encouraged to improve service competencies, optimize digital-based promotional activities, and continuously evaluate customer satisfaction to support sustainable business performance.